2016
DOI: 10.4081/aiua.2015.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Male sexual dysfunction in patients with chronic end-stage renal insufficiency and in renal transplant recipients

Abstract: The ED in patients with end stage chronic kidney failure (CKF) continues to have a strong prevalence, either in the patients who are undergoing dialysis or in those who have received transplants. In literature this issue is not sufficiently considered if not at all. Hypotestosteronemia is a risk factor for the onset of ED in end stage CKF patients. A significantly lower prevalence of hypogonadism among dialyzed patents and transplant recipients suggests that renal transplantation may be protective for the sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 32 publications
4
36
1
4
Order By: Relevance
“…In this sample, 29 kidney transplant recipients reported no sexual activity in the previous 4 weeks (20.9%), which is consistent with other studies, although lower than the percentage (35%) found by Antonucci et al (2015) in male individuals. It is thus important to identify the reason behind the lack of sexual activity for a long period of time.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this sample, 29 kidney transplant recipients reported no sexual activity in the previous 4 weeks (20.9%), which is consistent with other studies, although lower than the percentage (35%) found by Antonucci et al (2015) in male individuals. It is thus important to identify the reason behind the lack of sexual activity for a long period of time.…”
Section: Discussionsupporting
confidence: 92%
“…ESRD also has a strong impact on the sexual functioning of both men and women, clearly affecting their quality of life (Raggi et al, 2012) and leading to sexual dysfunction, which is a very common, benign, underdiagnosed, and multifactorial condition. Its risk factors (both physiological and psychological) are similar for both men and women (Antonucci et al, 2015). Some studies show that kidney transplantation improves sexual functioning by correcting metabolic and endocrine imbalances and improving psychological problems (Filocamo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is as a result of a difficulty or an interpersonal difficulty [1]. Many studies have been carried throughout the world on erectile dysfunction in the USA [2], in Italy [3] [4] and in France [5] [6] [7]. It occurs more and more in the general population but is pronounced in some individuals like those with chronic kidney diseases [7].…”
mentioning
confidence: 99%